2008
DOI: 10.2135/cropsci2007.06.0332tpg
|View full text |Cite
|
Sign up to set email alerts
|

Development of Genetic and Genomic Research Resources for Brachypodium distachyon, a New Model System for Grass Crop Research

Abstract: Grass crop genomics research frequently is hindered by large genome sizes and polyploidy. While rice is an attractive system for grass genomics due to its small genome size and available genome sequence, it is not particularly well-suited as a robust model system for all grass crops. The wild grass species Brachypodium distachyon (L.) P. Beauv. (Brachypodium) has recently gained favor as a new model system for grass crop genomics research because it possesses a suite of biological traits desired in a model sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
158
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(164 citation statements)
references
References 82 publications
5
158
0
1
Order By: Relevance
“…As reviewed previously, brachypodium possesses characteristics required for an effective plant model, including small stature, self-fertilization (but able to be cross-fertilized), rapid generation time, a compact genome and high transformation efficiency (Garvin, 2008;Vogel and Bragg, 2009;Vain, 2011;Brkljacic et al, 2011).…”
Section: Brachypodium As a Monocot Modelmentioning
confidence: 99%
“…As reviewed previously, brachypodium possesses characteristics required for an effective plant model, including small stature, self-fertilization (but able to be cross-fertilized), rapid generation time, a compact genome and high transformation efficiency (Garvin, 2008;Vogel and Bragg, 2009;Vain, 2011;Brkljacic et al, 2011).…”
Section: Brachypodium As a Monocot Modelmentioning
confidence: 99%
“…Brachypodium has a number of physical attributes that make it suitable for a model organism, such as a small genome, diploid strains, short life cycle, transformability, and small size [9][10][11]. In addition to a complete genome sequence, additional genetic and molecular resources include an expressed sequence tag and bacterial artificial chromosome libraries, microarrays, collections of natural strains, and the development of mutant populations (http:// www.brachypodium.org/).…”
Section: Introductionmentioning
confidence: 99%
“…1), but a vernalization treatment reduces this variability by reducing the time needed for winter-annual accessions to flower [10,11,15,16]. Information concerning the loci responsible for flowering-time differences in natural Brachypodium accessions is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The species of the genus Brachypodium have small chromosomes of variable number (x = 5, 7, 8, 9 or 10), making them unusual among the members of the Pooideae, which tend to have large chromosomes and base number of 7 (Shi et al 1993;Draper et al 2001;Hasterok et al 2004Hasterok et al , 2006Idziak and Hasterok 2008;Garvin et al 2008). Although ecotypes of B. distachyon with 10, 20 and 30 chromosomes have been described, some authors have indicated that these numbers do not represent a simple autopolyploid series (Robertson 1981).…”
Section: Introductionmentioning
confidence: 99%